ผลการใช้ควิซออนไลน์รายสัปดาห์ต่อพฤติกรรมการเรียนรู้ด้วยตนเองและเจตคติของผู้เรียน ระดับปริญญาบัณฑิต ในรายวิชาการควบคุมน้ำหนัก - เตชะสุขถาวร, วรัญญา (Journal of Education Studies, Chulalongkorn University, 2019)
The purposes of this research were to investigate the self-directed learning behavior and attitude of students when using a weekly online quiz. The research tools were comprised of 1) ten weekly online quiz sets with multiple choice answers on the Blackboard system, 2) a set of 20 questions evaluating the self-directed learning behavior questionnaire, adapted from the Self-directed Learning Readiness Scale, and 3) a set of ten questions for evaluating the attitude of students when using weekly online quiz questionnaire. One hundred and twenty-three subjects were recruited from undergraduate students who enrolled in the Weight Control Course during Semester 2, of 2015. The data collection included distributing the self-directed learning behavior questionnaire in weeks 2, 7, and 12 while the attitude questionnaire was distributed in weeks 2 and 12. The self-directed learning behavior evaluation result, was analyzed by Repeated ANOVA three times and illustrated at differet level, but none were significant. Data pertaining to student’s attitudes between two periods was analyzed by Paired t-test. This finding showed that weekly online quiz helped students to reduce their reading time during midterm and final examination periods. In conclusion, the weekly online quiz did not affect the self-directed learning behavior, however, it could support student’s time management skill to reduce reading time during examination periods.